2020
DOI: 10.1002/jbm4.10432
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Receptor Mediates a Myriad of Biological Actions Dependent on Its 1,25‐Dihydroxyvitamin D Ligand: Distinct Regulatory Themes Revealed by Induction of Klotho and Fibroblast Growth Factor‐23

Abstract: The hormonal vitamin D metabolite, 1,25‐dihydroxyvitamin D [1,25(OH)2D], produced in kidney, acts in numerous end organs via the nuclear vitamin D receptor (VDR) to trigger molecular events that orchestrate bone mineral homeostasis. VDR is a ligand‐controlled transcription factor that obligatorily heterodimerizes with retinoid X receptor (RXR) to target vitamin D responsive elements (VDREs) in the vicinity of vitamin D‐regulated genes. Circulating 1,25(OH)2D concentrations are governed by PTH, an inducer of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 162 publications
(299 reference statements)
0
29
0
1
Order By: Relevance
“…Vitamin D has been associated with different extraskeletal effects, due to the vitamin D receptor (VDR) being present in a wide variety of cells in the body [ 4 , 5 ] and influencing the regulation of more than 2000 genes [ 6 ]. While vitamin D deficiency has been associated with multiple diseases, not all of these associations have been verified [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D has been associated with different extraskeletal effects, due to the vitamin D receptor (VDR) being present in a wide variety of cells in the body [ 4 , 5 ] and influencing the regulation of more than 2000 genes [ 6 ]. While vitamin D deficiency has been associated with multiple diseases, not all of these associations have been verified [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because previous studies observed Cyp24a1 induction and Cyp27b1 suppression in mouse kidneys during a stay in orbit, [6][7][8] our data indicate that the expression profile of vitamin D 3 regulators, which is modulated by the space-travel environment, is preserved for at least 2 days after the return to Earth. We also found reduced expression of the Bglap gene, which is known to be activated by vitamin D 3 signaling to produce the bone matrix protein osteocalcin, 31 in the bone of space-traveled mice (Figure 2b). The changes in Fgf23 and Bglap gene expression in the bone samples support the contention that active vitamin D 3 levels in the plasma are decreased by space travel, which results in bone mass reduction.…”
Section: Effects Of Space Travel On Kidney Morphology and The Nrf2 Pathwaymentioning
confidence: 71%
“…In rodents, however, there is clear evidence of Klotho enhancement by vitamin D ( Table2 ). To explain this therapeutic effect, the complex interactions underling FGF23/Klotho/vitamin D homeostasis must be considered, as recently reviewed ( Haussler et al, 2020 ; Neyra et al, 2021 ).…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%
“…PPAR-γ agonists: Chen LJ, et al, 2014 ; Cheng et al, 2017 ; Huang KC, et al, 2014 ; Maquigussa et al, 2018 ; Shen et al, 2018 ; Zhang H, et al, 2008. mTOR inhibitors: Mizusaki et al, 2019 ; Tabibzadeh, 2021 ; Tataranni et al, 2011 ; Zhao Y, et al, 2015. Vitamin D: Haussler et al, 2020 ; Kuro-o, 2019 ; Lerch et al, 2018 ; Tsujikawa al., 2003. Antidiabetic drugs: Manrique et al, 2016 ; Liu W, et al, 2017, 2021; Son et al, 2019 ; Wang Q, et al, 2019 ; Yossef et al, 2020 ; Xue et al, 2019 .…”
Section: Approaches To Klotho-based Therapymentioning
confidence: 99%